Standards for letters of credit according to Islamic views - El Alimi, Mubarok; Elmuhriani, Wira (Junal Ilmu Manajemen, 2024)
In this increasingly modern era, there have been many big changes in various sectors which were previously carried out face to face, but now many conveniences have been provided due to changes in the current business climate. As we know, the world of exports and imports continues to be a special attraction in the field of implementation, so with the increasing complexity in a business, there must also be standards or benchmarks that become the basis for carrying out these economic activities, so that they remain on track. which is still permitted by the Islamic religion today. In this research, we use library research. The literature used in this research is from various books and relevant previous research journals as the basis for writing this article. From this research it can be concluded that Letter of Credit (L/C) is a payment method that is considered the safest in international trade transactions, because it provides security for both parties, namely exporters and importers. This method can also be adopted and applied by sharia banking, which generally uses wakalah contracts as the basic basis for its transactions. Fatwa of the National Sharia Council of the Indonesian Ulema Council No: 10/DSNMUI/IV/2000 concerning Wakalah provides guidelines regarding how the wakalah contract should be implemented in muamalah activities in society. The strong legal foundation of wakalah contracts strengthens their application in sharia banking, supports the development of sharia banking products and services based on wakalah contracts, and motivates the development of sharia banking in Indonesia.